Shock and Objectivity in Modern Times: Some Thoughts about Bauhaus Architecture. (2nd August 2020) - Goetzmann, Lutz
Abstract : 2019 marked the centenary of the Bauhaus movement. I took this anniversary as an opportunity to visit the new Bauhaus Museum in Weimar with friends. Here, however, I was surprised by the tormenting boredom that I felt during the visit. I experienced the building in the Bauhaus style as bleak, lifeless and ugly. My mood changed when a movie recording of Schlemmer's Triadic Ballet reminded us of World War I soldiers, the so‐called war‐tremblers, and I had intuitively related the very factual Bauhaus style to the war traumas of the Bauhaus generation. At that moment I saw the museum as a memorial to the victims of World War I, and I discovered parallels between trauma defence in the form of a mechanical lifestyle and the Bauhaus aesthetics, characterized by objectivity, typification and standardization. Against this background, I understand Bauhaus aesthetics in response to the triplicity of traumatic modernity, that is, to the primary helplessness, the death of God and the disasters of war. My thesis is that this architectural answer to the traumatic modernity remains valid until today, explaining the great success of the Bauhaus in modern times.